Bridging the readability gap: corporate disclosure trends - Keskin, Halit; Yalcin, Haydar; Esen, Emel (EMERALD GROUP PUBLISHING LTD, 2026)
PurposeCorporate readability-the ease with which stakeholders comprehend a company's written communications-is essential for fostering transparency, trust, and informed decision-making. In financial services, including banking, clear and accessible corporate disclosures are critical for regulatory compliance, customer relations, and institutional credibility. This study emphasizes the present-day importance of the readability gap-the persistent mismatch between the complexity of corporate disclosures and stakeholders' ability to understand them- and examines the evolution of corporate readability research across different countries over several decades, highlighting its relevance to financial services marketing and discussing its alignment with Sustainable Development Goals (SDGs).Design/methodology/approachThis study adopts a quantitative bibliometric literature review approach based on metadata analysis rather than a systematic literature review. Using data from the Web of Science Core Collection, 1,714 documents published between 1981 and 2025 were analyzed with Bibliometrix in R and Python-based network analysis tools.FindingsThe findings reveal notable disparities between developed and developing countries in corporate readability research. Developed economies, such as the United States and the United Kingdom, have prioritized readability in financial disclosures, particularly in the context of regulatory transparency and investor relations, contributing to institutional trust and market stability (SDG 16). In contrast, developing countries, including China and India, have increasingly focused on the role of digital transformation in corporate readability, particularly in sustainability and financial reporting (SDG 12). Additionally, addressing linguistic diversity and financial literacy challenges in emerging markets supports SDG 10 by promoting equitable access to corporate information.Practical implicationsThe study highlights the importance of improving readability strategies to enhance stakeholder engagement across industries, including financial services. For financial institutions, ensuring clarity in customer communications, financial reports, and regulatory disclosures can enhance trust and long-term relationships. In developing markets, leveraging digital tools and multilingual communication strategies can help bridge information gaps and improve financial literacy, fostering greater transparency and market participation.Social implicationsEnhancing corporate readability contributes to a more inclusive and transparent business environment, which is particularly relevant in sectors such as banking, insurance, and financial services, where trust and comprehension are critical. By improving the accessibility of corporate disclosures, organizations can support financial inclusion, responsible consumption, and sustainable governance practices.Originality/valueThis study is among the first to provide a comprehensive bibliometric analysis of corporate readability research, clearly outlining how it differs from previous studies by integrating a global scope, linking to SDGs, and offering sector-specific implications for financial services. It identifies key trends and regional differences with broad implications for business communication and financial services marketing. By aligning readability with SDGs, the study underlines its importance in promoting transparency, trust, and informed decision-making in corporate and financial contexts.
Keywords: Corporate readability; Bibliometric analysis; Financial communication; Stakeholder trust; Sustainable development goals; SOCIAL-RESPONSIBILITY; INFORMATION; GOVERNANCE; Business & Economics